Reading and understanding research - Locke, Lawrence F.; Silverman, Stephen J.; Spirduso, Waneen Wyrick (SAGE, 2010)
The only text of its kind to offer a practical 12-step process, this thoroughly-updated resource explains the basics of a research paper, how to look at the credibility of the research, how to select and read research with a critical eye, and how to understand the different types of research